2005
DOI: 10.1093/brain/awh481
|View full text |Cite
|
Sign up to set email alerts
|

Adult chronic sleepwalking and its treatment based on polysomnography

Abstract: Adult sleepwalking affects 2.5% of the general population and may lead to serious injuries. Fifty young adults with chronic sleepwalking were studied prospectively. Clinical evaluation, questionnaires from patients and bed partners, and polysomnography were obtained on all subjects in comparison with 50 age-matched controls. Subjects were examined for the presence of psychiatric anxiety, depression and any other associated sleep disorder. Isolated sleepwalking or sleepwalking with psychiatric disorders was tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
104
1
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 163 publications
(112 citation statements)
references
References 33 publications
3
104
1
4
Order By: Relevance
“…Authors concluded that treating any comorbid SDB also resolved sleepwalking in young adults. 22 • Four reports of large mixed case series included patients with sleepwalking but did not report all outcomes separately for the sleep walking patients. One series included 61 patients treated with clonazepam, 28 of them having night terrors/sleep walking, and 83.6% of the 61 were reported as achieving "rapid and sustained control".…”
Section: Resultsmentioning
confidence: 99%
“…Authors concluded that treating any comorbid SDB also resolved sleepwalking in young adults. 22 • Four reports of large mixed case series included patients with sleepwalking but did not report all outcomes separately for the sleep walking patients. One series included 61 patients treated with clonazepam, 28 of them having night terrors/sleep walking, and 83.6% of the 61 were reported as achieving "rapid and sustained control".…”
Section: Resultsmentioning
confidence: 99%
“…Informed consent forms were collected with signatures. (1)(2)(3)(4) to determine mild, moderate or severe symptomatology of each dissociative disorder symptoms. Each of the five symptoms has a severity scale of 4 and maximum score is 20.…”
Section: Data Collection Toolmentioning
confidence: 99%
“…Although parasomnia is frequently seen during childhood, it subsides in the adulthood. Reduced N3 phase Sleep and Central Nervous System (CNS) maturation with age can be the reason behind the decreased parasomnia incidence in adulthood [1][2][3]. Although there are limited number of studies, parasomnia in the adulthood is mostly related to psychiatric diseases and medical conditions [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study by Guilleminault et al, four out of five subjects placed on clonazepam had limited results at 3 months follow-up, reporting only a decrease in the frequency of sleepwalking events under particularly high daytime stress [63]. Cases of remission after treatment with olanzapine [64] and biperiden [65] have been reported.…”
Section: Sleepwalkingmentioning
confidence: 99%